From an Engraving to a Virtual Reconstruction: The 3D Modelling of Maria Amalia of Saxony's Funerary Ceremony in the Cathedral of Barcelona (1761). - Prieto Hames, Pablo (International Journal of Humanities & Arts Computing: A Journal of Digital Humanities, 2024)
This article discusses a virtual reconstruction of the catafalque and the ephemeral decorations created for the funeral of Maria Amalia of Saxony in the Cathedral of Barcelona in 1761. A combination of a historical-artistic approach and a variety of 3D modelling techniques has made it possible to recreate an ephemeral piece of architecture that, being constructed only for the funerary ceremony, has not lasted over time, such that the work presented here constitutes a novel strategy to promote a better understanding of another element of our cultural legacy.